Making sense of the middle ground: shared value in nascent social entrepreneurship - Osorio-Vega, Patricio (2016)
Whilst social entrepreneurship is widely accepted as an issue of critical and contemporary importance, why and how social and economic aspects of value coexist within the phenomenon remain elusive. Current attempts to address this complexity tend to insist on the presumption that social and economic imperatives are distinct concerns that need to be combined, trying to unveil strategies to manage tension in social enterprises (hybridity approach) or piecemeal factors that could satisfactorily explain social (and environmental) orientation in entrepreneurship (sustainability approach). Recent work has highlighted the need to address the possibility of mutually constitutive configurations, where the nexus between social and economic imperatives is not a trade-off but a symbiosis. However, this increasing attention remains largely theoretical. This thesis addresses this gap by empirically examining the construct of shared value creation (SVC) in social entrepreneurship. Through this lens, the nexus between social orientation and economic self-interest becomes a third aspect of value with its own underpinnings.